Citizen’s Level of Participation and Satisfaction in the Conduct of Barangay Assembly: A Case of One Philippine LGU - Arrabaca, Franesa Jeanne Castil; Base, Renato L. (Jurnal Ilmiah Peuradeun, 2020)
The purpose of this paper was to examine the extent of citizen’s participation and satisfaction in local governance in view of the powers of barangay assembly as stated in the Local Government Code of the Philippines (Republic Act No. 7160). This study aims at exploring the dynamic interplay of citizen’s satisfaction in the conduct of barangay assembly relative to their participation to said assembly as platform towards participatory local governance. Based on the results of our study, we recommended that LGU participation and regular attendance in barangay assemblies should be intensified, along with that, citizen’s participation and satisfaction right after the conduct of the assembly should have feedback mechanism, and based on the findings of our study we present policy implications and insights essential for the enhancing what is contain in Chapter 6 of the Local Government Code of the Philippines.